Revitalization of Islamic Religious Education Through Teacher Professionalism in the Digital Age - Mufarrichatuz Zakiyah; Muhamad Arif (Prodi PAI STIT Sunan Giri Bima, 2025)
The revitalization of Islamic Religious Education (IRE) is a strategic effort to strengthen its role in adapting to the digital era's technological advances. This study aims to describe the revitalization of IRE through the professionalism of IRE teachers at MTsN Gresik, outlining their strategies to enhance professionalism and identify challenges faced. Employing a qualitative case study approach, data were collected through interviews, observations, and documentation, analyzed using pattern matching, explanation building, time-series analysis, and repeated observations. Findings reveal that IRE teachers enhance professionalism by leveraging technologies such as Smart TVs, PowerPoint, Canva, Quizizz, Google Classroom, and AI for interactive learning, engaging in continuous training, and collaborating via the Teacher Subject Discussion Group (MGMP). The madrasah supports this through digital-focused training and workshops. Challenges include limited digital facilities, insufficient direct interaction in online learning, and uneven technological proficiency among teachers. Solutions involve capacity building and cross-stakeholder collaboration to support digital transformation in education. This study contributes to understanding IRE teacher professionalism in the digital era, offering practical insights for technology-based learning strategies, although its scope is limited to one madrasah, suggesting broader future research.